Fluid balance and outcome in critically ill patients with traumatic brain injury (CENTER-TBI and OzENTER-TBI): a prospective, multicentre, comparative effectiveness study. Issue 8 (August 2021) - Wiegers, Eveline Janine Anna; Lingsma, Hester Floor; Huijben, Jilske Antonia; Cooper, David James; Citerio, Giuseppe; Frisvold, Shirin; Helbok, Raimund; Maas, Andrew Ian Ramsay; Menon, David Krishna; Moore, Elizabeth Madeleine; Stocchetti, Nino; Dippel, Diederik Willem; et al.
Summary: Background: Fluid therapy—the administration of fluids to maintain adequate organ tissue perfusion and oxygenation—is essential in patients admitted to the intensive care unit (ICU) with traumatic brain injury. We aimed to quantify the variability in fluid management policies in patients with traumatic brain injury and to study the effect of this variability on patients' outcomes. Methods: We did a prospective, multicentre, comparative effectiveness study of two observational cohorts: CENTER-TBI in Europe and OzENTER-TBI in Australia. Patients from 55 hospitals in 18 countries, aged 16 years or older with traumatic brain injury requiring a head CT, and admitted to the ICU were included in this analysis. We extracted data on demographics, injury, and clinical and treatment characteristics, and calculated the mean daily fluid balance (difference between fluid input and loss) and mean daily fluid input during ICU stay per patient. We analysed the association of fluid balance and input with ICU mortality and functional outcome at 6 months, measured by the Glasgow Outcome Scale Extended (GOSE). Patient-level analyses relied on adjustment for key characteristics per patient, whereas centre-level analyses used the centre as the instrumental variable. Findings: 2125 patients enrolled in CENTER-TBI and OzENTER-TBI between Dec 19, 2014, and Dec 17, 2017, were eligible for inclusion in this analysis. The median age was 50 years (IQR 31 to 66) and 1566 (74%) of patients were male. The median of the mean daily fluid input ranged from 1·48 L (IQR 1·12 to 2·09) to 4·23 L (3·78 to 4·94) across centres. The median of the mean daily fluid balance ranged from −0·85 L (IQR −1·51 to −0·49) to 1·13 L (0·99 to 1·37) across centres. In patient-level analyses, a mean positive daily fluid balance was associated with higher ICU mortality (odds ratio [OR] 1·10 [95% CI 1·07 to 1·12] per 0·1 L increase) and worse functional outcome (1·04 [1·02 to 1·05] per 0·1 L increase); higher mean daily fluid input was also associated with higher ICU mortality (1·05 [1·03 to 1·06] per 0·1 L increase) and worse functional outcome (1·04 [1·03 to 1·04] per 1-point decrease of the GOSE per 0·1 L increase). Centre-level analyses showed similar associations of higher fluid balance with ICU mortality (OR 1·17 [95% CI 1·05 to 1·29]) and worse functional outcome (1·07 [1·02 to 1·13]), but higher fluid input was not associated with ICU mortality (OR 0·95 [0·90 to 1·00]) or worse functional outcome (1·01 [0·98 to 1·03]). Interpretation: In critically ill patients with traumatic brain injury, there is significant variability in fluid management, with more positive fluid balances being associated with worse outcomes. These results, when added to previous evidence, suggest that aiming for neutral fluid balances, indicating a state of normovolaemia, contributes to improved outcome. Funding: European Commission 7th Framework program and the Australian Health and Medical Research Council.